Pelanggaran Prinsip Kemanusiaan terhadap Tawanan Perang di Penjara Abu Ghraib Ditinjau dari Konvensi Jenewa 1949 - Triansyah, Zuhri; Saadah, Maratun (Uti Possidetis: Journal of International Law, 2022)
This article discusses forms of legal responsibility regarding violations of humanitarian principles in humanitarian law against the treatment of prisoners of war in Abu Ghraib prison in terms of the Geneva convention of 1949. Legal liability is an obligation that arises from violations committed by individuals or the state because they are considered contrary to the law or conventions. applicable. This article uses a normative juridical method with the main source being legal materials containing normative legal rules. The results of the discussion of this article show that the principle of state responsibility related to human rights violations is realized by taking legal action against individual perpetrators and providing compensation to victims and is regulated in the Geneva Conventions. Second, the United States is responsible for the provisions stipulated in the Geneva Conventions of 1949 concerning violations of humanitarian principles by bringing to justice the perpetrators who have violated humanitarian principles through the United States military court.